Determination of an efficient technological process of manufacturing various support elements for functional surfaces - Gayda, S.V.; Salapak, L.V.; Lesiv, L.E. (Forestry, Forest, Paper and Woodworking Industry, 2021)
Designs were developed and a technical description was made of the supporting elements of the functional planes of lattice furniture of a square section with the overall dimensions of 740x54x54mm for comparison. A method of studying production processes of manufacturing support elements with the texture of beech wood has been developed. Technological processes have been built with the selection of modern equipment for the production of support elements. A comparison of the developed technological processes was made. The necessary materials and equipment are calculated to produce 3 types of modern support elements of the functional planes of lattice furniture of a certain design. Routes of technological processes were developed and shop layouts for three supporting elements of different structures were presented. The economic feasibility and effectiveness of the selected option, i.e. one of the three for a certain support element for the functional plane of lattice furniture, were calculated. Numerical calculation of all options showed the following, that the third option for manufacturing supporting elements with a wood texture of a square section (54x54 mm) with a length of 740 mm is optimal, where the cost of equipment is 857.22 thousand UAH, the number of employees is 10 , the total power is 33.75 kW. It should also be noted that the third option produces the least rhubarb waste, in particular, in the amount of 98.19 m3, and the cost of materials for a set of legs in the amount of 4 pieces is the lowest, which is 380 hryvnias. compared to other options. The highest value of the economic efficiency indicator is for the third option of investment investments, which is 0.202. The payback period for this option is 4.96 years. In this version of the production of support elements with the texture of wood with a square cross-section, the lowest cost is quite acceptable (11,089.36 thousand hryvnias). The same applies to the profit received under this option (1,996.08 thousand hryvnias). The positive thing is that this option has the smallest capital investment (9,896.84 thousand UAH). Therefore, the third option for the production of supporting elements for the functional planes of lattice furniture, in which the base is made of three slats glued in layers from chipboard with a thickness of 16 mm with a square section of 48 (16 × 3) mm × 48 mm, and the cross-section of the legs is made of beech veneer with a thickness of 3 mm is the most effective and attractive for production.